NṞTYA GAṈAPATI: INSIGHTS FROM LITERATURE, ICONOGRAPHY AND BHARATANATYAM - Vadivelou, K.; George, Saju (ShodhKosh: Journal of Visual and Performing Arts, 2024)
In Hinduism, dance is a ritual, and deities like Siva and Krishna are depicted as dancers. The Bhakti period in South India facilitated the development of music and dance as avenues to praise God and attain salvation or eternal bliss. Lord Siva, particularly, is revered as the God of dance, and various dancing forms of other Gods are present in Hindu Mythology alongside Nataraja. Gaṇapati worshipped as the remover of obstacles, is specifically praised as Nartana Gaṇapati in his dancing form. The Agamas enumerates sixteen forms of Gaṇapati, with Nṛtya Gaṇapati, the dancing form, being one of them. References in Vināyakar Parākkiramam and numerous literary works elaborate on different aspects of Gaṇapati's dance. Presently, Bharatanatyam performances incorporate kritis, slokas, and songs dedicated to Nartana Gaṇapati. This form is established and venerated in Siva and Gaṇapati temples, often depicted through sculptures nationwide. This article delves into numerous literary references and temple depictions to enhance comprehension of Gaṇapati as a dancer and the incorporation of Nṛtya Gaṇapati in Bharatanatyam.